PTH-120 In vivo assessment of foods that stimulate intestinal secretions: implications for dietary advice in ileostomy care. (17th June 2017) - Major, G; Wilkinson-Smith, V; Murray, K; Ashleigh, L; Hoad, C; Marciani, L; Gowland, P; Spiller, R; ,
Abstract : Introduction: Plant foods may stimulate intestinal secretion through chemicals designed to deter herbivores such as lactucins in lettuce and rhein in rhubarb. Increased small bowel water increases ileostomy output and may induce diarrhoea in people with an intact bowel. The aim of the study was to investigate the effect of lettuce and rhubarb on intestinal water content. Method: Design: a three period, three treatment, crossover trial. Population: adults≥18 without bowel disorders. Interventions: 3 meals of 245±3 kcal, taken with 200 mL water. Meals used: 1) 2 slices white bread with 10g butter (10g fat); 2) 300g cooked rhubarb with 60 mL lactose free cream (22.5g fat); 3) 300g Romaine lettuce with 30 mL mayonnaise (23.5g fat). Meals were eaten one week apart to minimise carryover. The order of meals was randomised using a remote, internet based program. Primary outcome: water content of the small bowel (SBWC) using magnetic resonance imaging (MRI). Secondary outcomes: ascending colon water content and T1 relaxation time (T1AC), an MRI constant reflecting water content; visual analogue scales of bloating and satiety (0–100). MRI analysts were blind to the test meal. Scans were taken fasting and 0, 60, 120, 180 min postprandial. Symptoms were scored every 30 min. Results: 15 subjects completed the study between October 2016 - February 2017. 9 were female, 6 male, median age 21(IQR 20, 22) and mean body mass index 21.4kg.m -2 (SD ±2.2). Bread induced a fall in SBWC compared to a rise after lettuce and a greater rise after rhubarb, with significant differences in the area under the curve (0–3 hours) of the change from baseline (p<0.01 for each paired t-test). Ascending colon water volumes were low (0–15 mL) but at 3 hours were significantly higher for both lettuce and rhubarb than bread (p<0.05 for both, Wilcoxon). Only rhubarb induced a rise in T1AC but differences at 3 hours did not reach significance (p=0.06 for both). Bloating scores were higher for lettuce > rhubarb > bread, with scores after lettuce and bread still significantly different at 2 hours. Satiety scores were higher immediately after lettuce. Figures show mean±SEM. Conclusion: MRI allows assessment of both small and large bowel fluids. Lettuce and rhubarb meals increased small bowel water with later effects on the ascending colon on the arrival of meal residue. Rhubarb may also influence T1 in the colonic chyme. These data demonstrate a mechanism by which food can alter stoma output and stool consistency. Future work is needed to identify the active components of these meals. Disclosure of Interest: None Declared